Optimization of Productive Zakat Distribution through the Linggau Makmur Program in MSME Empowerment: A Case Study on BAZNAS of Lubuklinggau City - M. Romi Junaidi; Muhammad Saleh; Aris Sutrisno; Peny Cahaya Azwari (International Journal of Community Engagement Payungi, 2025)
Small and medium enterprises (SMEs) are significant drivers of economic development in Indonesia, especially in creating job opportunities and promoting growth. However, SMEs face various challenges, particularly in accessing financial resources, which can hinder their expansion. As an Islamic socio-economic instrument, Zakat has great potential to support community empowerment. When managed effectively, productive Zakat can alleviate poverty and improve welfare. This study focuses on optimizing productive zakat distribution through the Linggau Makmur program by BAZNAS Lubuklinggau City, which aims to enhance the welfare of mustahik (zakat recipients), specifically those involved in SMEs. The research uses a qualitative approach with a descriptive design, collecting data through semi-structured interviews with BAZNAS officials, mustahik, and stakeholders. The study identifies key factors influencing zakat distribution effectiveness, challenges faced, and strategies for improving the program’s impact. Findings suggest that the Linggau Makmur program has significantly empowered SMEs by providing financial assistance, training, mentoring, and continuous support. However, challenges like limited funding and low financial literacy among recipients remain. The study provides practical recommendations for optimizing zakat distribution to ensure long-term economic independence for mustahik and sustainable development.